1974
DOI: 10.1192/bjp.124.4.336
|View full text |Cite
|
Sign up to set email alerts
|

Two Syndromes of Suicide

Abstract: People who kill themselves are grouped together as suicides on the basis of that one action, yet they can hardly be considered to be a homogenous class. Attempts to define sub-categories among suicides can be made in a number of different ways, none by itself entirely satisfactory. Differentiation by psychiatric diagnosis is one possibility, but is difficult to achieve and throws little light on the undoubted contribution of social factors. Sociological studies have usually persisted in regarding all suicides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(26 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…In Bristol Seager and Flood's (1965) reported that 41% of suicides contacted their GPs in 4 weeks before death, but it was 65% in Edinburgh (Ovenstone and Kreitman, 1974), 59% in Sussex (Barraclough et al, 1974), 39% in Australia (Chynoweth et al, 1980), and 36% in Bristol when re-examined by Vassilas (1993). The current study's figure of 21% is lower than those reported in previous studies.…”
Section: Interpretations Of Findingsmentioning
confidence: 99%
“…In Bristol Seager and Flood's (1965) reported that 41% of suicides contacted their GPs in 4 weeks before death, but it was 65% in Edinburgh (Ovenstone and Kreitman, 1974), 59% in Sussex (Barraclough et al, 1974), 39% in Australia (Chynoweth et al, 1980), and 36% in Bristol when re-examined by Vassilas (1993). The current study's figure of 21% is lower than those reported in previous studies.…”
Section: Interpretations Of Findingsmentioning
confidence: 99%
“…O 'Connor et al (1999) argued that there had been little progress in classi®cation of suicide since Ovenstone and Kreitman's (1974) identi®cation of two syndromes, one being`acutely disrupted', the other`chronically disorganised' with a history of parasuicide. Bagley et al (1976) proposed three types: depressive, sociopathic, and suicide associated with physical illness.…”
Section: Categorisation Of Reasons For Suicidementioning
confidence: 99%
“…In treatment trials of DSH it is important to assess repetition of DSH as an outcome because it is common (Bancroft & Marsack, 1977 ;Sakinofsky, 2000) and has a strong association with eventual suicide (Ovenstone & Kreitman, 1974 ;Hawton & Fagg, 1988 ;Foster et al 1997 ;Sakinofsky, 2000). In a recent systematic review of problem-solving interventions for DSH patients, repetition was used as the outcome in a meta-analysis of the results of these treatments (Hawton et al 1998(Hawton et al , 2000.…”
Section: Introductionmentioning
confidence: 99%